2020
DOI: 10.3390/app10134515
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Positive Effect of Bicarbonate Addition on Growth and Photosynthetic Efficiency of the Green Microalgae Chlorella Sorokiniana (Chlorophyta, Trebouxiophyceae)

Abstract: Bicarbonate ions are the primary source of inorganic carbon for autotrophic organisms living in aquatic environments. In the present study, we evaluated the short-term (hours) effects of sodium bicarbonate (NaHCO3) addition on the growth and photosynthetic efficiency of the green algae Chlorella sorokiniana (211/8k). Bicarbonate was added to nonaxenic cultures at concentrations of 1, 2, and 3 g L−1 leading to a significant increase in biomass especially at the highest salt concentration (3 g L−1) and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 60 publications
(78 reference statements)
1
18
0
Order By: Relevance
“…Due to their fast growth rate, these microorganisms can be easily cultured in closed bioreactors or open systems and achieve high biomass yields [12], and their cultivation does not compete for resources used in conventional agriculture [13]. Photosynthesis in microalgae is similar to that in higher plants, although characterized by a higher yield compared to terrestrial crops, as it is more efficient in transforming solar energy into chemical energy [14,15]. However, microalgal photosynthesis and growth can be affected by several factors, including light supply, temperature, pH, inorganic carbon availability, salinity, and nutrients [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to their fast growth rate, these microorganisms can be easily cultured in closed bioreactors or open systems and achieve high biomass yields [12], and their cultivation does not compete for resources used in conventional agriculture [13]. Photosynthesis in microalgae is similar to that in higher plants, although characterized by a higher yield compared to terrestrial crops, as it is more efficient in transforming solar energy into chemical energy [14,15]. However, microalgal photosynthesis and growth can be affected by several factors, including light supply, temperature, pH, inorganic carbon availability, salinity, and nutrients [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Photosynthesis in microalgae is similar to that in higher plants, although characterized by a higher yield compared to terrestrial crops, as it is more efficient in transforming solar energy into chemical energy [14,15]. However, microalgal photosynthesis and growth can be affected by several factors, including light supply, temperature, pH, inorganic carbon availability, salinity, and nutrients [15][16][17][18]. Particularly, among nutrients, nitrogen (N) is considered one of the most critical for plant-cell growth, since it is a constituent of proteins such as peptides, enzymes, chlorophylls, and energy-transfer molecules [16,19].…”
Section: Introductionmentioning
confidence: 99%
“…The content in α tocopherol, carotene, and lutein is 112, 600, and 4300 μg/g of dry matter, respectively [ 11 ]. HPLC analysis of the Chlorella sorokiniana 211/8k strain confirmed the presence of high levels of carotenoids, among which are neoxanthin, β-carotene, and high levels of lutein (~60% of total carotenoids) [ 12 ]. All these compounds have high radical scavenging properties [ 11 ] and suggest such an alga as a possible source of exogenous antioxidants.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were presented by Jegan et al [52], who obtained the highest optical density (0.477) in C. vulgaris cultures at the highest dose of sodium bicarbonate (2 M). Different results were presented by Salbitani et al [48], who analysed the effect of three doses of NaHCO 3 (1, 2 and 3 g•L -1 ) on the growth of the microalgae Chlorella sorokiniana and found no significant differences between the values obtained at the highest dose and in the control object. The experiment was conducted over 72 h; it represents the short-term effect of bicarbonate addition on algae cultures.…”
Section: Biomass Production With Co2 From Sodium Bicarbonatementioning
confidence: 80%
“…An increase in biomass was also observed at lower doses of bicarbonate, which may be due to the beneficial effect of NaHCO 3 on photosynthesis and cellular component accumulation. A study by Salbitani et al [48] confirmed the positive relationship between bicarbonate, the chlorophyll a content and the photosynthetic activity of Chlorella sorokiniana. The use of NaHCO 3 may be an alternative to CO 2 , which decreases the pH of culture medium and may reduce the availability of carbon for photosynthesis [49].…”
Section: Biomass Production With Co 2 From Sodium Bicarbonatementioning
confidence: 86%